2021
DOI: 10.1080/0092623x.2021.1944937
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Insecurities and Sexual Coercion in Same- and Cross-Gender Couples: The Mediational Role of Couple Communication Patterns

Abstract: The use of subtle strategies to have sex with an unwilling partner is harmful to a couple's sexual well-being but these strategies remain understudied. This research examined the mediating role of communication patterns in the associations between attachment insecurities and sustained sexual coercion in 145 same-and cross-gender couples, and the moderating role of partners' gender. In addition to actor and partner effects, results revealed significant indirect effects from attachment insecurities to sexual coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…However, such examples go beyond the aim of the current study and would warrant further examination of the thoughts and behaviors of partners during conflicts. For instance, recent research has demonstrated that higher attachment anxiety is associated with more criticizing and blaming during couple conflicts, whereas higher attachment avoidance is related to more defensiveness, withdrawal, or refusal to discuss the issue (Bonache et al, 2019; Dugal et al, 2021). In turn, these behaviors have been recognized as being associated with lower relationship satisfaction (Donato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such examples go beyond the aim of the current study and would warrant further examination of the thoughts and behaviors of partners during conflicts. For instance, recent research has demonstrated that higher attachment anxiety is associated with more criticizing and blaming during couple conflicts, whereas higher attachment avoidance is related to more defensiveness, withdrawal, or refusal to discuss the issue (Bonache et al, 2019; Dugal et al, 2021). In turn, these behaviors have been recognized as being associated with lower relationship satisfaction (Donato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely recognized theoretical frameworks of the intrapersonal and dyadic processes that underlie relationship satisfaction is attachment theory (Mikulincer & Shaver, 2016). Indeed, researchers and clinicians have recognized that attachment security (or insecurity) can shape how romantic partners experience conflicts (Dugal et al, 2021; Prager et al, 2015), which, in turn, can either enhance relationship satisfaction or jeopardize the relationship (Ogolsky & Gray, 2016; Woodin, 2011).…”
Section: Introductionmentioning
confidence: 99%